An Assessment of IELTS Speaking Test - Shahzad Karim; Naushaba Haq (International Journal of Evaluation and Research in Education (IJERE), 2014)
The present study focusses on assessing the speaking module of IELTS. The assessment discusses both positive aspects and weaknesses in IELTS speaking module. The researcher has also suggested some possible measures for the improvement in IELTS speaking module and increasing its validity and reliability. The researcher has analysed and assessed IELTS speaking module in the light of both theoretical and practical perspectives presented by experienced researchers in the field of language testing and evaluation. The researcher’s major concern in the assessment of IELTS speaking module is to do utmost effort to avoid the element of subjectivity and to present some logical and practical suggestions for improving IELTS speaking module. DOI: http://dx.doi.org/10.11591/ijere.v3i3.6047